Penerapan teknologi memperbaiki kualitas ampas kelapa sebagai pakan ternak di Kabupaten Wajo - Wahyuti Wahyuti; Juni Astuti (Seminar Nasional Pengabdian Kepada Masyarakat, 2018)
This Community Partnership Program (PKM) is about Implementing Technology to Improve the Quality of Coconut Dregs as Fodder in Majauleng District, Wajo Regency of South Sulawesi. The program started in March 2018. Business opportunity of producing fodder from coconut dregs is very promising in Paria village. The implementation of technology is needed to increase the benefits, quality and value of coconut dregs which will increase family income. Based on the identified problems, this program propose solutions to solve them. First, collective counseling. The community is gathered to listen the explanations and discuss about the benefits of implementing technology in processing fodder from coconut dregs. Next, collective training. The training is about processing coconut dregs starting from collecting coconut dregs, steaming/ drying, microbial mixing, cooling, drying, and packaging. Approaches used in this program are participatory approaches, group approaches, individual approaches, lecturing, and discussion. The participatory approach was used so the group members actively participate in this program. The group approach was used to hold counseling, training/ processing simulations, then further activity is done with individual approach. The results obtained were the fremented and dried coconut dregs which was very effective as an alternative for fodder compared to coconut dregs without any treatment (fermented or dried). The fermented coconut dregs is preffered since it is easy to make with urea-based fertilizer, Em4 animals, yeast and rumen of cattle (if any). When the groups have extra ingredients, they can dry them under the sunlight. The result of fermented coconut dregs have promising prospects in the future.